Pengaruh Sistem Pengendalian Internal dan Kinerja Karyawan Terhadap Efektivitas Pemberian Kredit pada Perusahaan Perbankan - Paramitra Caroline; Fajar Gustiawaty Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of the control environment, risk assessment, control activities, information and communication, monitoring, and employee performance of the effectiveness of credit granting at the banking companies in BUMN Bank. Data collection methods are done by survey and questionnaires. The number of respondents in this study was 40 respondents, in distributing questionnaires using purposive sampling technique. Based on the F test used to test whether the regression model used is fit, if the significant value>α = 0.05 then the hypothesis is rejected, which means the regression model is not fit. If the significant value <α = 0.05, the hypothesis is accepted, which means the fit regression model. F test results show a significant value of 0,000 which means less than 0.05 then the hypothesis is accepted, which means four independent variables namely the control environment (X1), information and communication (X4), monitoring (X5), and employee performance (X6) simultaneously have a positive effect and risk assessment (X2), control activities (X3) simultaneously have a negative effect on the dependent variable, namely the effectiveness of credit (Y). From the results of the t test it can be seen that four independent variables namely the control environment (X1), risk assessment (X2), control activities (X3), information and communication (X4), monitoring (X5), and employee performance (X6) have a partially positive and negatuve effect on the dependent variable namely the variable the effectiveness of granting credit (Y) because it has a significantly smaller value of 0.05